2011
DOI: 10.1016/j.talanta.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Label-free, arrayed sensing of immune response to influenza antigens

Abstract: Periodic outbreaks of pandemic influenza have been a devastating cause of human mortality over the past century. More recently, an avian influenza strain, designated H5N1, has been identified as having the potential to cause a zoogenic pandemic in humans, and a current outbreak of a new H1N1 influenza variant hypothesized to be of swine origin is of considerable concern. In order to facilitate surveillance and the rapid assessment and comparison of vaccination efforts, a high-throughput assay is highly desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Spatially separated probe spots of approximately 100 μm in diameter can be easily resolved, and the technique is therefore useful for multiplexed detection. 29,30 …”
Section: Introductionmentioning
confidence: 99%
“…Spatially separated probe spots of approximately 100 μm in diameter can be easily resolved, and the technique is therefore useful for multiplexed detection. 29,30 …”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have developed influenza whole-protein and peptide antigen microarray platforms for the determination of antibody reactivity to conformational and linear epitopes of influenza hemagglutinin (HA). Other groups have reported array-based systems to measure the reactivity of a variety of HA-binding antibodies, including arrays generated with random peptides that can be used to measure the antibody response to influenza vaccination [11], [12], [13]. These studies demonstrate the potential value of an array-based approach.…”
Section: Introductionmentioning
confidence: 89%
“…6 The technique has also been validated via comparisons to reference methods including surface plasmon resonance (SPR) and spectroscopic ellipsometry. 7 With regard to influenza-targeted applications, we have demonstrated that multiplex hemagglutinin arrays have utility for rapidly assessing human serum samples for the presence of anti-influenza antibodies in a vaccine trial, 8 and provide a simple method for multiplex serology on avian surveillance samples. 9 Here, we provide a preliminary description of an AIR array intended to simplify the task of classifying newly observed strains of influenza, by enabling patterns of reactivity with the chip to be compared with those generated by known strains of the virus.…”
Section: Bound Probementioning
confidence: 99%